Diversity and abundance of bacterial and fungal communities in rhizospheric soil from smallholder banana producing agroecosystems in Kenya - Wahome, Caroline N.; Maingi, John M.; Ombori, Omwoyo; Njeru, Ezekiel Mugendi; Muthini, Morris; Kimiti, Jacinta Malia (Frontiers in Horticulture, 2023)
In agroecosystems, microbial communities play a crucial role in delivery of various ecosystem services. These microbial communities are affected by several factors such as soil physicochemical properties which contribute to the diversity of bacterial and fungal communities. In this study, we investigated the soil physicochemical parameters and the diversity and abundance of bacterial and fungal communities in rhizospheric soil collected from banana growing regions in Kisii, Nyamira and Embu Counties of Kenya. Rhizospheric soil samples from the three regions showed significant differences at (P= 0.01) with the lowest recorded pH being 4.43 in Embu County. Based on Next-generation sequencing results, there was a significant diversity and abundance of bacterial division Proteobacteria while the predominant fungal division was basidiomycota, Several genera in the fungal division such as Penicillium and Cladosporium as well as bacterial division such as Acidobacterium and Pseudomonas sp. were those associated with soil. There were several plant pathogenic and beneficial bacteria and fungi. Based on a Redundancy analysis (RDA) the distribution of these microbes was affected negatively by soil parameters such as total organic carbon (TOC) and pH. In conclusion, Soil health and continuous mono-cropping systems play a significant role in the diversity and abundance of both beneficial and harmful soil microbes. Metagenomics approaches in studying microbial communities in agroecosystems is a revolutionary approach which will aid in the development of sustainable tools in agriculture that improve microbiome structures as well as overall productivity.